FREQUENCY OF ANTI-HCV, HBsAg AND RELATED RISK FACTORS IN PREGNANT WOMEN AT NISHTAR HOSPITAL, MULTAN - Taseer, Ijaz -ul-Haque; Ishaq, Fozia; Hussain, Laiq; Safdar, Sohail; Ahsanullah, M; Mirbahar, Mirbahar; Faiz, Shakeel A. (Journal of Ayub Medical College Abbottabad, 2010)
Background: Viral hepatitis is a global issue. Among the hepatitis viruses hepatitis B and C are important in South Asia including Pakistan. There are various modes of transmission of these viruses. Vertical transmission is also gaining importance. Antepartum screening for HBV and HCV would help the infected women for appropriate antiviral therapy at appropriate time as well as for taking proper care of the newborns. The present study was designed to see the frequency of HBsAg and anti-HCV in pregnant women at Nishtar Hospital, Multan. Methods: This was a cross-sectional study carried out using non-probability purposive sampling technique. The period of the study was from June 2006 to August 2007. Five hundred (500) pregnant women attending outpatient department of Gynaecology and Obstetrics were included. Informed consent was taken. A specially designed proforma was filled in. Anti-HCV and HBsAg were tested by device method. Data were analyzed on SPSS-11. Results: Out of 500 pregnant women 35 (7.00%) were found to be anti-HCV positive and 23 (4.60%) were positive for HBsAg. Mean age was 26.7±4.8 years. Majority of the patients 263 (52.60%) were in the age group 26-35 years. 138 (27.60%) women were nulliparous and 282 (56.40%) were para 1-4 and anti-HCV and HBsAg were common in this parity group. Only 80 (16.00%) women were para 5 or more. All anti-HCV and HBsAg positive women were house-wives. Most of them were belonging to rural areas having poor socio-economic status. Among 35 anti-HCV positive women, 20 (57.14%) had history of previous surgery, while 13 (37.14%) had history of multiple injections, 5 (14.28%) received blood transfusion, 4 (11.42%) had ear/nose piercing while tattooing was seen in only 2 (5.71%). Among 23 HBsAg positive women, 10 (43.47%) had history of previous surgery. History of multiple injections was present in 6 (26.08%) patients, 4 (17.39%) patients had history of blood transfusion, tattooing, ear/nose piercing, history of dental procedure, history of sharing needles was observed in 1 each. Conclusion: Frequency of anti-HCV is more common than HBsAg in our study population. Previous history of surgery, multiple injection therapy and blood transfusion were observed as risk factors among anti-HCV and HBsAg positive pregnant women. Keywords: Anti-HCV, HBsAg, Hepatitis B, Hepatitis C, pregnancy